Legal Protection of Copyright in the Form of Illustrations in Decision Number 988 K/Pdt.Sus-HKI/2021 - Venia Utami Keliat; Yordandi Eykel Harapenta Ginting (International Journal of Social Science and Religion (IJSSR), 2026)
This study analyzes the legal protection of copyright for illustrations under Law Number 28 of 2014 concerning Copyright and Examines the Implications of Supreme Court Decision Number 988 K/Pdt.Sus-HKI/2021 on legal certainty in Indonesia. Illustrations, as works of fine art, are protected automatically once embodied in a tangible form and include both moral and economic rights of the creator. This research employs a normative juridical method, drawing on statutory and case law. Primary legal materials consist of copyright legislation and relevant court decisions, while secondary materials include legal literature, journals, and doctrines related to intellectual property law. The analysis is conducted qualitatively by interpreting legal norms and considering judicial considerations. The results show that Indonesian Copyright Law protects the principles of automatic protection, recognition of moral and economic rights, and preventive and repressive legal mechanisms. The Supreme Court emphasized that copyright recordation is not absolute proof of ownership if conducted in bad faith. Protection is granted only to parties who are legally and factually entitled to the work. The decision strengthens legal certainty by prioritizing good faith and substantive justice in copyright disputes.